Prevalence of Lower Back Pain among Dentists in Kurdistan Region-Iraq - Nabeel Abdulrazzaq Fattah (Erbil Dental Journal, 2025)
Background and Objective: Lower back pain caused by professional activities often develops over time due to repetitive work. Dentists are particularly prone to low back discomfort because of their working posture during patient treatment, as they spend most of their workday in static, uncomfortable positions. This study aimed to investigate the incidence of risk factors for low back pain in dentists and examine the potential relationship between these factors and working posture.